Design And Build A Mobile-Based Daily Prayer Learning Application (Case Study: MTS Al Hidayah Limabangan) - Nugraha, Yopi (RISTEC : Research in Information Systems and Technology, 2021)
The development of technology is currently growing rapidly and as we know in this day and age many junior high school students a re using sma rtphones and used to commucate with their parents or just for pla y gamming. During the covid-19 pandemic, the use of smartphones by junior high school students is increa sing due to the need for online lea rning activities from home. There are many kinds of daily prayer lea rning books but because junior high school students use their sma rtphones more often than reading books. With the creation of mobile-based daily prayer lea rning application, it is hoped that it can help junior high school students in learning daily prayers trough their sma rtphones which they can lea rn anywhere and anytime. The method used in the design of this application is using agile method. The results of this study a re mobile-ba sed daily prayer lea rning application designed to suit the needs of the MTS Al Hidayah Limbangan school in which there a re daily prayers in arabic, la tin of a rabic written, and their meaning so that they can be easily understood.